Accumulation of a nod gene inducer, the flavonoid naringenin, in the cytoplasmic membrane of Rhizobium leguminosarum biovar viciae is caused by the pH-dependent hydrophobicity of naringenin. - Recourt, K (1989)
Most Sym plasmid-localized nodulation genes of Rhizobium leguminosarum bv. viciae are only expressed upon activation of the NodD protein by plant flavonoids, e.g., naringenin (S. A. J. Zaat, C. A. Wijffelman, H. P. Spaink, A. A. N. van Brussel, and B. J. J. Lugtenberg, J. Bacteriol, 169:198-204, 1987). As part of a study on the mechanism of NodD protein activation, the mechanism of uptake and the intracellular fate of [3H]naringenin were studied. Naringenin was accumulated by Rhizobium cells without apparent metabolic conversion to an 80-fold-higher concentration in a process which did not require any of the other Sym plasmid-localized nod genes. Naringenin accumulation was nonsaturable, highly reversible, and not inhibited by the presence of other flavonoids or the metabolic inhibitors potassium cyanide, sodium azide, 2,4-dinitrophenol, and carbonyl cyanide m-chlorophenylhydrazone. These data indicate an accumulation mechanism without high affinity sites which does not use cellular energy. In vitro, naringenin has high affinity for the cytoplasmic membrane. This binding was pH dependent, very high at pH 5.7 and not present anymore at pH 9.7. A similar pH dependency was found for the affinity of naringenin for the olive oil fraction of a biphasic olive oil-water system. pH-dependent changes in the UV spectrum indicate ionization of naringenin at high pH to a negatively charged form. Since it has recently been shown that the nodD gene product is located in the cytoplasmic membrane (H. R. M. Schlaman, H. P. Spaink, R. J. H. Okker, and B. J. J. Lugtenberg, J. Bacteriol., in press), our data are consistent with a model in which the un-ionized form of naringenin accumulates in the cytoplasmic membrane and activates, in a metabolically unaltered form, the NodD protein.